2021
DOI: 10.1186/s12877-021-02568-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing trends in potentially inappropriate medications in older people: a nationwide repeated cross-sectional study

Abstract: Background Potentially Inappropriate Medications (PIMs) and polypharmacy are widely used indicators of suboptimal prescribing for older people. The aim of this study was to describe the changes in the prevalence of PIMs and polypharmacy among people aged 75 years and over between 2011 and 2019 in France. Methods PIMs and polypharmacy were assessed among people aged 75 years and over every two years between 2011 and 2019 using the French health insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 39 publications
2
24
2
Order By: Relevance
“…First, polypharmacy was common among older adults in our study. However, the observed prevalence of polypharmacy (23.5%) is lower than those reported from previous studies conducted in France and in other developed countries [ 21 23 ]. This can be explained by the heterogeneous measurements of the number of medications taken and also by different study populations.…”
Section: Discussioncontrasting
confidence: 75%
“…First, polypharmacy was common among older adults in our study. However, the observed prevalence of polypharmacy (23.5%) is lower than those reported from previous studies conducted in France and in other developed countries [ 21 23 ]. This can be explained by the heterogeneous measurements of the number of medications taken and also by different study populations.…”
Section: Discussioncontrasting
confidence: 75%
“…Second, international comparisons of psychotropic indicators are complicated due to differences in national drug formula across countries, for example no psycholeptics/psychoanaleptics combinations (ATC: N05C) are approved in Sweden. Last, we report a lower prevalence of excessive polypharmacy than most previous studies ( Drusch et al, 2021 ). This is mainly explained by the use of a 1-day point prevalence in our study, that can be compared with the 3 and 12-month periods used in most other studies ( Masnoon et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 48%
“…To the best of our knowledge, this is the first study to assess the trends of polypharmacy and PIM use in older Chinese lung cancer outpatients with multimorbidity. Previous studies based on national representative surveys have shown an alarming increase in the polypharmacy trends in the United States (from 8.2% in 1999 to 15% in 2012; Kantor et al, 2015 ), Sweden (from 16.9% in 2006 to 19.0% in 2014; Zhang et al, 2020 ), and France (from 44.9% in 2011 to 47.8% in 2019; Drusch et al, 2021 ), which are consistent with regional register-based studies on this period in the United Kingdom (a polypharmacy increase from 11.2% in 1995 to 22.8% in 2010; Guthrie et al, 2015 ) and those using the University Groningen IADB.nl prescription database in the Netherlands (showing an increase from 56.5% in 2012 to 58.2% in 2016; Oktora et al, 2021 ). Subjective measures, such as sleep diaries and anxiety and depression screening scales, also assist the diagnosis.…”
Section: Discussionmentioning
confidence: 96%